Points A, B, and C are given in the coordinate plane. There exists a point Q and a constant k such that for any point P,
PA² + PB² + PC² = 3PQ² + k.
If A = (4,-4), B = (3,8), and C = (-1, 2), then find the constant k.
Given points \( A = (4, -4) \), \( B = (3, 8) \), and \( C = (-1, 2) \), and a point \( Q \) such that for any point \( P \) in the plane, the following equation holds:
\[
PA^2 + PB^2 + PC^2 = 3PQ^2 + k
\]
We need to find the constant \( k \).
### Step 1: Write down the expression for the sum of squares of distances
Let \( P = (x, y) \) and \( Q = (x_Q, y_Q) \). The squared distances from \( P \) to the points \( A \), \( B \), and \( C \) are:
\[
PA^2 = (x - 4)^2 + (y + 4)^2
\]
\[
PB^2 = (x - 3)^2 + (y - 8)^2
\]
\[
PC^2 = (x + 1)^2 + (y - 2)^2
\]
The sum of these squared distances is:
\[
PA^2 + PB^2 + PC^2 = \left[(x - 4)^2 + (y + 4)^2\right] + \left[(x - 3)^2 + (y - 8)^2\right] + \left[(x + 1)^2 + (y - 2)^2\right]
\]
Expanding these expressions:
\[
PA^2 = (x^2 - 8x + 16) + (y^2 + 8y + 16)
\]
\[
PB^2 = (x^2 - 6x + 9) + (y^2 - 16y + 64)
\]
\[
PC^2 = (x^2 + 2x + 1) + (y^2 - 4y + 4)
\]
Adding them together:
\[
PA^2 + PB^2 + PC^2 = \left[3x^2 + (-8x - 6x + 2x) + (16 + 9 + 1)\right] + \left[3y^2 + (8y - 16y - 4y) + (16 + 64 + 4)\right]
\]
Simplifying:
\[
PA^2 + PB^2 + PC^2 = 3x^2 - 12x + 26 + 3y^2 - 12y + 84
\]
Thus:
\[
PA^2 + PB^2 + PC^2 = 3(x^2 - 4x + \frac{26}{3}) + 3(y^2 - 4y + 28)
\]
### Step 2: Express the right-hand side
The expression for \( 3PQ^2 \) is:
\[
3PQ^2 = 3\left[(x - x_Q)^2 + (y - y_Q)^2\right] = 3\left[(x^2 - 2xx_Q + x_Q^2) + (y^2 - 2yy_Q + y_Q^2)\right]
\]
Expanding:
\[
3PQ^2 = 3x^2 - 6xx_Q + 3x_Q^2 + 3y^2 - 6yy_Q + 3y_Q^2
\]
### Step 3: Set up the equation
We equate \( PA^2 + PB^2 + PC^2 \) with \( 3PQ^2 + k \):
\[
3x^2 - 12x + 110 + 3y^2 - 12y + 84 = 3x^2 - 6xx_Q + 3x_Q^2 + 3y^2 - 6yy_Q + 3y_Q^2 + k
\]
By comparing coefficients, we get:
\[
-12x = -6xx_Q \quad \text{and} \quad -12y = -6yy_Q
\]
So:
\[
x_Q = 2, \quad y_Q = 2
\]
Now, matching the constant terms:
\[
110 + 84 = 3x_Q^2 + 3y_Q^2 + k
\]
\[
194 = 3(2^2) + 3(2^2) + k = 12 + 12 + k = 24 + k
\]
Thus:
\[
k = 194 - 24 = 170
\]
### Final Answer:
The constant \( k \) is \( \boxed{170} \).